Divisions of labor : globality, ideology, and war in the shaping of the Japanese labor movement - Carlile, Lonny E. (University of Hawaii Press, 2005)
Divisions of Labor positions the ideological and organizational evolution of the Japanese labor movement within the larger historical currents that shaped and organized labor globally in the twentieth century. Interspersing detailed narratives of Japanese labor history with analyses of parallel developments in Western European and international labor movements, Lonny Carlile shows how world views and labor movement strategies were shared across national boundaries and shaped in similar ways in the industrialized West and East. Beyond this, he highlights how in both Western Europe and Japan issues that had divided labor since the 1920s were central to the Cold War, which kept labor movements at odds with themselves internally in systematically similar ways. His book suggests that, to the extent that the historical courses of labor movements diverged, this was as much a uh_product of differences in geopolitical location as any inherent cultural or nationally specific ideological tendency. The volume's approach brings to the fore an important new dimension to our existing understanding of post-World War II Japanese labor and political history by outlining the connection between the politics of Japanese labor and the structure and dynamics of global politics. In addition, by drawing out these parallels and similarities, it provides thought-provoking insights into twentieth-century labor movements in general. Divisions of Labor will be of interest not only to students and specialists of Japan and East Asia, but also to readers with a more general interest in labor history and politics, diplomatic history, Cold War history, comparative politics, and sociology.